Strategi Mahasiswa dalam Merevitalisasi TPQ Nurul Iman: Studi Kasus Desa Jayakarta, Kabupaten Bengkulu Tengah - Jeni Puspitasari; Ricardo Anggi Saputra; Fitri Kurnia; Nicken Aristha; Pita Apia Ningsih; Rara Aziza; Galih Budiatna; Rahmatul Fadillah; Angly Mayori; Sandi Fadli; Resna Tia Afina (Pusat Riset dan Inovasi Nasional, 2024)
Al-Quran education park is one of the informal institutions in the field of religious education that is currently developing in the midst of society. With the development of each TPQ both in quality, quantity and even a good administrative system does not guarantee TPQ to be one of the routine places for children in the process of reading and writing the Koran. One example is TPQ Nurul Iman which is located in Jayakarta Village, Talang Empat District, Central Bengkulu Regency, Bengkulu Province. This TPQ is in an environment with the quantity of parents and children both leading to continue to study and understand the Koran, it's just that the TPQ rarely operates due to several factors. The purpose of this research is to revitalize TPQ Nurul Iman so that it can be used and operate properly like the function of TPQ in general. The method used in this research is the Qualitative method by conducting observations and interviews to explore in-depth information about existing problems. In this activity, several conclusions can be drawn, namely: First, with the revitalization program carried out by KKN students, it is expected to be able to maintain the quantity and quality of the TPQ. Second, it is hoped that with the hearings conducted by students with the TPQ and village officials, they will be able to pay more attention to TPQ and provide additional teaching staff so that there will be no worries for parents in entrusting their children to TPQ Nurul Iman. Third, with the revitalization that occurs, it is hoped that later the TPQ can operate according to its function and not experience a vacuum again.